Get Health‘e’: A Pilot Test of a Digital Health Literacy Intervention for Young Adults - Jennifer A. Manganello; Kimberly F. Colvin; Molly Hadley; Kelsey O'Brien (Health Literacy Research and Practice)
Background Young adults face a number of health concerns and are typically beginning to manage their health on their own. At the same time, this age group is more connected to digital technology than ever before, and studies show that young adults can struggle with digital health literacy skills. Objective The online Get Health‘e’ Program consists of six modules addressing digital health literacy skills, including topics such as internet searches and social media. This study evaluates the program based on a usability and pilot study. Methods Recruited participants ranged in age from 18 to 24 years and were predominantly White women. After an eligibility screening, half of the participants were randomly assigned to the program group. All 131 participants were administered two surveys, 2 weeks apart; the program group had access to the program for that week. Survey questions included demographics, the eHealth Literacy Scale (eHEALS), and six sets of five multiple-choice questions assessing digital health knowledge. Key Results Both groups showed an improvement of 1.0 points on the eHEALS scale, but a repeated measures analysis comparing scores for the program and control groups indicated no significant difference in score improvement between the two groups, F(1, 129) = 0.003, p = .96. The program group had an average improvement in quiz scores (from pre to post) from 1.6 to 2.3 which was better than score improvement in the control group across the six modules. The majority of participants in the program group found the program to be useful (67.2%) and informative (59.4%), and 93.8% said they would recommend it to someone they know. Conclusions The Get Health‘e’ program was well received by participants and led to an increase in digital health knowledge. Programs like this have the potential to raise awareness among youth about how to access and evaluate health information online. [HLRP: Health Literacy Research and Practice. 2024;8(4):e224–e235.]